Managing Destinations From Theories to Practices - Scott, Noel (Emerald Publishing Limited, 2024)
Topics covered include policy, planning and strategy, stakeholders, new markets, infrastructure, transport and research and knowledge transfer with contributions from countries as diverse as Brazil, Croatia, Italy, Portugal, Russia, Saudi Arabia, and Spain
Description based on publisher supplied metadata and other sources
Keywords: Tourism-Marketing; Tourism-Management